Obtenção de rochas sintéticas a partir de resíduos de vidro comercial e pó de granito - Nociti, Denyse Meirelles [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This paper was intended to produce and characterize synthetic rocks in a microstructural, mechanical and fractographic way. Such rocks were obtained from the mixture of commercial glass waste and granite powder. This research was divided in two steps: in the first one it was to determined the amount of materials used in the mixture and the sintering temperature in order to produce synthetic rocks with higher mechanical strength and lower energy consumption, while in the second the synthetic rocks were submited to some tests, such as roughness measurement, flexural strength, fracture toughness by the SEVNB method, hardness, wettability and apparent porosity. In this first step two compositions were defined in order to produce the samples. The first composition contained 1/3 of granite powder, 1/3 of ambar glass waste and 1/3 of transparent glass waste; the second one contained 60% of granite powder, 30% of ambar glass waste and 10% of transparent glass waste. It was also determined the sintering temperature: 850ºC for the first composition and 1050ºC for the second one. Other tests, such as: X-ray diffraction, scanning electron microscopy, thermogravimetric analysis and differential scanning calorimetry were also performed. The results of the experiments in the second step were compared to andorinha, an ordinary kind of Brazilian gray granite and showed that synthetic rocks are very promising and viable. Synthetic rocks presented lower wettability and porosity values and higher flexural strength and hardness values, when compared to the samples of andorinha. It could be concluded that the first composition was the most relevant from the commercial point of view (1/3 of granite powder, 1/3 of ambar glass waste and 1/3 of transparent glass waste) for it presents higher flexural strength value and lower sintiring temperature value. This represents a considerable economic gain

O objetivo deste trabalho foi a produção e caracterização microestrutural, mecânica e fractografica de rochas sintéticas, obtidas por fabricação, a partir da mistura de resíduos dos pós de granito e vidro comercial. Esta pesquisa foi dividida em duas etapas. Na primeira etapa, a meta foi determinar a composição a ser utilizada na mistura e a temperatura de sinterização que produzisse uma rocha sintética com maior resistência mecânica e menor consumo de energia. Nesta fase foram definidas duas composições para produção das amostras: a primeira com massa de 1/3 de pó de granito, 1/3 de pó de vidro âmbar e 1/3 de pó de vidro transparente e uma segunda composição, com 60% de pó de granito, 30% de pó de vidro âmbar e 10% de pó de vidro transparente. Tais amostras foram sinterizadas em temperaturas que variaram de 800ºC a 1100ºC, e com base nos resultados obtidos pelo ensaio de flexão de três pontos, foi determinada para primeira composição, uma temperatura de sinterização de 850ºC e para a segunda 1050ºC. Na segunda etapa da pesquisa, aprofundou-se os estudos com relação às rochas sintéticas obtidas, realizando-se medidas de rugosidade, resistência a flexão, tenacidade a fratura pelo método SEVNB (Single-edge V-notch Beam), microdureza, molhabilidade e porosidade aparente. Além de difração de raios X, microscopia eletrônica de varredura e análise termogravimétrica e calorimetria diferencial de varredura. Os resultados obtidos nesta segunda etapa foram comparados com o granito comercial andorinha e mostraram que as rochas sintéticas obtidas são altamente promissoras e viáveis. As rochas sintéticas produzidas a partir das duas composições, apresentam menores valores de molhabilidade e porosidade e maiores valores de tensão de ruptura à flexão e microdureza, quando comparados as amostras do gra... (Resumo completo, clicar acesso eletrônico abaixo)
Synthetic rocks produced from commercial glass waste and granite powder
Keywords: Vidro; Granito; Resíduos sólidos; Microestrutura; Fractografia; Reaproveitamento (Sobras, refugos, etc.); Rochas igneas; Glass